Global im-possibilities exploring the paradoxes of just sustainabilities - Godfrey, Phoebe; Buchanan, Mary (Just sustainabilities, 2023)
"At a time when environmental and social stakes are at their highest--with rising crises and contradictions at the nexus of a growing sense of environmental and social collapse--there are no easy solutions. Global Im-Possibilities explores examples of what can be done around the world to ameliorate this dynamic. Via a range of essays and a multitude of case studies, this book explores what new lessons can be learned from examining the challenges and impediments to achieving just sustainabilities on the levels of policy, planning, and practice, and considers how these challenges and impediments can be addressed by individuals and/or governments. Taking a nuanced approach, to provide an intersectional analysis of particular issues relating to the ideals for achieving sustainability, this book asserts that it is only in recognizing such complexity that we can hope to begin to achieve just sustainabilities"--Provided by publisher.